2020
DOI: 10.1016/j.dnarep.2019.102766
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the small oligonucleotide products of nucleotide excision repair in UVB-irradiated human skin

Abstract: UVB radiation results in the formation of potentially mutagenic photoproducts in the DNA of epidermal skin cells. In vitro approaches have demonstrated that the nucleotide excision repair (NER) machinery removes UV photoproducts from DNA in the form of small (~30-nt-long), excised, damage-containing DNA oligonucleotides (sedDNAs). Though this process presumably takes place in human skin exposed to UVB radiation, sedDNAs have not previously been detected in human skin. Using surgically discarded human skin, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…As we have previously reported ( Choi et al., 2020 ; Kemp et al., 2019 ), the addition of 20 μM SP (10 nmol) twice over 2 days to cell culture medium maintained below small, 8 mm human skin explants reduced epidermal XPB protein expression by 50 to >95%, depending on the individual skin sample ( Figure 1 a). In contrast, the addition of 20 μM SP topically on the skin did not affect XPB protein levels (data not shown).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As we have previously reported ( Choi et al., 2020 ; Kemp et al., 2019 ), the addition of 20 μM SP (10 nmol) twice over 2 days to cell culture medium maintained below small, 8 mm human skin explants reduced epidermal XPB protein expression by 50 to >95%, depending on the individual skin sample ( Figure 1 a). In contrast, the addition of 20 μM SP topically on the skin did not affect XPB protein levels (data not shown).…”
Section: Resultssupporting
confidence: 78%
“…Using cultured keratinocytes (KCs) in vitro, we found that both SP and Can induced replication stress and apoptosis but that these responses are not correlated with a loss of XPB protein. Coupled with previous research showing that SP-mediated loss of XPB negatively influences responses to UVR in the skin ( Choi et al., 2020 ; Kemp et al., 2019 ), these results indicate that high concentrations of SP and Can induce toxicity in epidermal skin cells through an XPB-independent mechanism.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mechanism by which SP induces the loss of XPB protein was initially investigated by Alekseev et al and was shown to occur rapidly after addition of SP to the culture medium and to be independent of XPB mRNA levels [3]. Several other groups have confirmed these general findings in different cell types in vitro and in tissues ex vivo and in vivo [37,48,62,64,65]. The effect of SP on XPB protein levels was also reversible, as XPB protein levels could be fully restored within a few hours of withdrawing the drug in vitro.…”
Section: Sp Promotes the Rapid Proteasomal Degradation Of Xpbmentioning
confidence: 92%
“…The observation that SP promotes the degradation of the critical DNA repair protein XPB might indicate that patients taking the drug orally or topically are at an elevated risk of skin cancer development in regions of sun-exposed skin. Though in vitro studies with keratinocytes and ex vivo studies with skin explants showed that SP can deplete these cells and tissues of XPB, inhibit UV photoproduct removal, and increase mutagenesis [37,65], epidemiological studies have found no evidence that SP use is associated with increased cancer risk of any cancer type, including in the skin [78]. There are several possible explanations for these observations, including the fact that orally administered SP is rapidly metabolized (Figure 3) by the liver into compounds [79] such as canrenone and 7α-thiomethylspironolactone (TMS) (Figure 2) that do not affect XPB protein levels [37,64].…”
Section: Implications For Sp In the Skin And Potential Risks Of Carcinogenesismentioning
confidence: 99%